Exploring the impact of sidestep cutting maneuvers at different angles on biomechanical parameters - Jamkrajang, P.; Thip-Osod, W.; Suwanmana, S.; Limroongreungrat, W.; Condello, G. (Journal of Physical Education and Sport, 2025)
This study aimed to evaluate kinetic and kinematic parameters during planned and unplanned sidestep cutting maneuvers performed at cutting angles of 45° and 90°. Twelve collegiate soccer players performed six successful trials for each task (three at a 45° angle and three at a 90° angle). Kinematic and kinetic data were recorded using ten optoelectronic cameras and a force plate, operating at sampling rates of 250 and 1000 Hz, respectively. A two-way repeated measures ANOVA was used to analyze the effects of task and angle. The findings revealed that the cutting angle significantly influenced ground reaction forces (GRFs) and lower limb joint kinematics at initial contact (IC) and maximum vertical GRF (max vGRF), while no significant differences were observed between the planned and unplanned tasks. Regarding kinetic parameters, 90° cutting maneuvers elicited higher lateral and vertical forces at IC and generated a greater posterior force at max vGRF compared to 45° cutting maneuvers. For kinematic parameters, 90° cutting maneuvers exhibited greater hip abduction angles at IC and more pronounced hip joint moments in flexion, abduction, and external rotation at IC and max vGRF. These factors can contribute to a higher knee flexion angle, greater knee abduction, and internal rotation moments at IC. Conversely, 45° cutting maneuvers produced greater knee flexion moments and inversion angles, resulting in improved force distribution. To optimize performance while minimizing injury risk, coaches should incorporate drills encompassing various cutting angles into their training programs. This will prepare athletes for the various cutting scenarios encountered during gameplay.